In vitro micropropogation Of Sphaeranthus amaranthoides Burm.F - Devika, R; Pillai, Justin Koil; Arockiamary, S Nazareth (Recent Research in Science and Technology, 2012)
Sphaeranthus amaranthoides commonly known as garden Lavender / Kesavardini is used to cure eczema, skin diseases, worm infestation, pile, aphrodisiac etc, from Ancient Era. In present investigation the auxillary buds and shoot tips were used as explants for invitro micropropogation. The initiation and best multiple shoots was developed at 4mg/L of BAP with a highest frequency of 70% and good root proliferation was observed at 2.0mg/L of IBA.